Patients’ awareness and knowledge of the root canal treatment in Saudi population: survey-based research - Doumani, Mazen; Habib, Adnan; Qaid, Nashwan; Abdulrab, Saleem; Bashnakli, Ahmad Reda; Arrojue, Ramakrishna (International Journal of Dental Research, 2017)
Endodontics is a profession based on the work with other people so several factors should be considered during clinical decision-making process.Objective: The aim of this study was to evaluate the knowledge and awareness of patients in a sample of Saudi population regarding endodontic treatment.Methods: multiple-choice questionnaire regarding knowledge and awareness of root canal treatment distributed to 227 patients, the questionnaire comprised questions ranged from personal and social details to specific questions about endodontic treatment; the analysis of data was performed using methods of descriptive statistics.Results: The results shown that the strong spontaneous toothache was the most impact factor of the need for endodontic treatment in (53%) of respondents, (29%) of subjects do not know anything about root canal treatment, (47%) of respondents indicated that the pain was the most important concern associated with the root canal treatment.Conclusion: Toothache is the greatest motivation of patient to refer the dentist, and pain is the more important patients’ concerns associated with root canal treatment, knowledge and awareness of patients regarding root canal treatment is different among races and populations.